The modeling of the Quranic alphabets’ correct pronunciation for adults and children experts - Ahmad, Salmiah; Syed Badruddin, Syarifah Nuratikah; Nik Hashim, Nik Nur Wahidah; Embong, Abd Halim; Altalmas, Tareq, M.; Shahbudin Hassan, Surul (IEEE, 2019)
The Quranic alphabets can be characterized from their point of articulation (Makhaarij) and their characteristics (Sifaat). The fact is that there is limited research in the field of Tajweed from the engineering perspective. This research focused on the identification and analysis of the correct pronunciation of the Quranic alphabets on the features obtained from adult and children experts. The combination of four formant frequencies (F1, F2, F3, F4) and three Power Spectral Density values (PSD1, PSD2, PSD3) were used as the features to represent the pronunciation of each alphabet for both categories. The validation was done through a Graphical User Interface (GUI) to record the new audio signal, processes and produces the outcomes of the pronunciation in the form of a percentage (%) of accuracy, as compared to the reference model of both experts’ categories.